The Existence of Heteroclinic Travelling Waves in the Discrete Sine-Gordon Equation with Nonlinear Interaction on a 2D-Lattice - Bak, S. (Журнал математической физики, анализа, геометрии, 2018)
The article deals with the discrete sine-Gordon equation that describes an infinite system of nonlinearly coupled nonlinear oscillators on a 2D-lattice with the external potential V (r) = K(1 - cos r). The main result concerns the existence of heteroclinic travelling waves solutions. Sufficient conditions for the existence of these solutions are obtained by using the critical points method and concentration-compactness principle. Статтю присвячено дискретному рiвнянню синус-Гордона, яке описує нескiнченну систему нелiнiйно зв'язаних нелiнiйних осциляторiв на двовимiрнiй гратцi iз зовнiшнiм потенцiалом V (r) = K(1 cos r). Основний результат стосується iснування розв язкiв у виглядi гетероклiнiчних рухомих хвиль. За допомогою методу критичних точок i принципу концентровано компактностi отримано достатнi умови iснування таких розв язкiв.